"A Besy Woman … and Full of Lawe": Female Litigants in Early Tudor Star Chamber. (October 2019) - Youngs, Deborah
Abstract: This article considers the opportunities available to, and the constraints to be negotiated by, female litigants at the court of Star Chamber during the reigns of the early Tudor kings. Star Chamber was a prerogative court and grew in popularity following the transformation and clarification of its judicial functions under Thomas Wolsey in the early sixteenth century. While it has suffered losses to its records, around five thousand cases still survive from the early Tudor period, including nearly one thousand cases involving female litigants. Unlike those in other Westminster courts, such as Common Pleas, Chancery, or the Court of Requests, Star Chamber cases have yet to be fully examined for what they can tell us about women's access to justice and their experience of legal process. This article begins by surveying the number of cases involving female litigants, showing that far more women came to the court as plaintiffs than as defendants. The numbers were significant—in line with Chancery—but still show women as a minority. Drawing on a wide range of examples, the paper explores the major factors determining, and limiting, women's active roles as litigants, taking into consideration cultural expectations, legal practice (including the operation of coverture), and, where detected, individual decision-making.